Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
[tex]x=-8, -1[/tex]
Step-by-step explanation:
Given the equation [tex]x^{2} +9x+8=0\\[/tex],
By the quadratic formula,
[tex]x=\frac{-b+-\sqrt{b^{2}-4ac } }{2a}[/tex],
[tex]x=\frac{-(9)+-\sqrt{(9)^{2}-4(1)(8) } }{2(1)}=\frac{-9+-\sqrt{49 } }{2}=\frac{-9+-7 }{2}[/tex]
We have two different solutions for x where [tex]x=\frac{-9-7 }{2}[/tex] and [tex]x=\frac{-9+7 }{2}[/tex]
So, x = [tex]-16/2=-8[/tex] and [tex]x=-2/2=-1[/tex]
Therefore, the solutions to this quadratic equation is x = -8, -1, by the quadratic formula.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.